The cinema-cognition dialogue: a match made in brain - Dudai, Yadin (Frontiers in Human Neuroscience, 2012)
That human evolution amalgamates biological and cultural change is taken as a given, and that the interaction of brain, body and culture is more reciprocal then initially thought becomes apparent as the science of evolution evolves (Jablonka & Lamb 2005). The contribution of science and technology to this process is probably the first to come to mind: the biology of Homo sapiens permits and promotes the development of artificial devices that in turn enable us to sense and reach physical niches previously inaccessible, hence extending the biological capabilities, while at the same time endowed with the potential to mould over time selective pressures on these innate capabilities. The jury is yet out on the pace in which critical biological changes take place in evolution, but there is no question that the kinetics of technological and cultural change is much faster, rendering the latter more important in the biography of the individual and at present, of the species alike. However, though the capacity of art to enrich human capabilities is recurrently tapped into by philosophers and critics (e.g. Arsitotle/Poetics, Richards 1925, Smith & Parks 1951, Gibbs 1994), less attention is commonly allotted to the role of the arts in the aforementioned ongoing evolutional tango. My position is that the art of cinema is particularly suited to explore the intriguing dialogue between art and the brain. Further, in the following set of brief notes, which goal is to merely to incite discussion, I posit that cinema provides an unparalleled and highly rewarding experimentation space for the mind of the individual consumer of that art, while at the same time providing a useful and promising device for investigating brain and cognition.